Recent changes in the US business cycle - Marcelle Chauvet; Simon Potter (Federal Reserve Bank of New York, 2001)
The U.S. business cycle expansion that started in March 1991 is the longest on record. This paper uses statistical techniques to examine whether this expansion is a onetime unique event or whether its length is a result of a change in the stability of the U.S. economy. Bayesian methods are used to estimate a common factor model that allows for structural breaks in the dynamics of a wide range of macroeconomic variables. We find strong evidence that a reduction in volatility is common to the series examined. Further, the reduction in volatility implies that future expansions will be considerably longer than the historical average.
Keywords: E52; C53; 330; Recession; Common Factor; Business Cycle; Bayesian Methods; Konjunktur; Zeitreihenanalyse; Bayes-Statistik; USA